(untitled) (Zaporizhzhia Historical Review, 2021)
The article is based on the analysis of Thomas Cromwell’s works on the development of the state governing in England of the first part of the XVI century. By 1532 he had become the king’s chief minister and was responsible for drafting most of the Acts of Parliament by which the Reformation was effected. He probably originated the idea of making the king supreme head of the church in England. The author investigates the process of the formation of the type of the statesman on the early absolutism stage.